Timoleague Franciscan Friary, north nave wall, tomb niche, jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
Jamb, arch and hood moulding of tomb niche. From intrados, moulding comprises quardant, right-angled rebate, quadrant. The hood, from outer moulding to inner, comprises a frontal fillet, hollow chamfer quadrant.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; roll moldings; moldings, hollow